Effect of Longan Leaf Extract (Dimocarpus longan L.) on Total Cholesterol and Hepatic Histopathology in Type 2 Diabetes Mellitus Mice - Akhsan, Ardhi; Kuswanti, Nur; Khaleyla, Firas (LenteraBio : Berkala Ilmiah Biologi, 2025)
Hypercholesterolemia occurring in type 2 diabetes mellitus can trigger chronic complications, one of which is liver damage. Longan leaves contain metabolites that function as antihyperlipidaemic agents and repair liver damage. This study used 24 male DDY mice divided into six groups: negative control (A), positive control (B), metformin (C), longan leaf extract at 28 mg/kg body weight (D), 42 mg/kg body weight (E), and 56 mg/kg body weight (F). Type 2 DM was induced orally with a high-fat diet (HFD) and alloxan administered intraperitoneally. Longan leaf extract was administered orally. Total cholesterol levels were measured using a cholesterol meter. Liver histological slides were prepared using paraffin methods and evaluated using a light microscope. Total cholesterol levels and liver histopathology were statistically significant. The results showed that the longan leaf extract significantly affected total cholesterol levels and liver histopathology (p<0.05). The 56 mg/kgBW dose of longan leaf extract yielded the best results for reducing total cholesterol levels by 17.25 and liver histopathology scores of 1.1. Therefore, longan leaf extract has the potential to be an antihypercholesterolemic agent and to improve liver damage.